Characterization Of Cambodian Clays And Their Suitability For Ceramic Tiles Applications - Bun , Kim Ngun (2012)
The present work is aimed to provide detail scientific data on characterization of Cambodian clays and their suitability for ceramic tiles applications. The study covered three parts – Part I deals with characterization of the properties of the raw clay samples, Part II deals with investigation on changes of the properties between bulk and clay fraction (< 2 μm), and Part III deals with optimization of ceramic tile compositions incorporating Cambodian clays by using statistical design technique. In Part I, the raw clay samples were characterized in terms of physical properties (particle size distribution, cation exchange capacity, consistency limits), chemical composition, mineralogical analysis, thermal property, and firing characteristics. Some of these data were plotted on the reference diagrams to evaluate the suitability of the Cambodian clays for various ceramic applications. In Part II, the bulk and clay fraction samples were characterized on their physical properties chemical composition, color of ceramic body after firing, transformation of phases after firing, microstructure of ceramic bodies, and relationships within the firing characteristics.Finally in Part III, the selected clay samples were mixed with the commercial feldspar and silica to formulate the tile body. Ten formulations were designed by using mixture experiment methodology. Regression models related to linear firing shrinkage (LFS), water absorption (WA) and modulus of rupture (MOR) were generated and analyzed. Results showed that the studied Cambodian clays present very high plastic behavior. There major oxides such as SiO2 (51 – 57 %), Al2O3 (≈ 22 %) and Fe2O3 (5 – 11 %) were observed in the clay samples. The main peaks from the mineralogical analysis were assigned to quartz, chlorite-vermiculite mixed-layer, illite and kaolinite. The evaluation diagrams illustrated that the Cambodian clays are most suitable for structural ceramics. The clay fraction samples showed the improvement of the specific surface area (SBET) and cation exchange capacity (CEC). values. Differences of oxides contents were found between the bulk and clay fraction samples. The oxides showing increment in the clay fractions are Al2O3, K2O, CaO and MgO, whereas those showing decrement are SiO2 and Fe2O3. Firing at ≥ 1050 oC led to the formation of new phases such as mullite and hematite for all the samples, and cristobalite for C1. Judging from the microstructure and firing characteristic data, firing temperature of 1050 oC is considered as the minimum for Cambodian clays. From the statistical analysis, the optimum mixture compositions for ceramic tile bodies incorporating Cambodian clays (C1 and C4) to meet the requirements of standard specifications were obtained. This study proves that the Cambodian clays are suitable as raw materials for the production of ceramic tiles.